Extraction of gaharu essential oil using microwave assisted extraction (MAE) - Mohd. Rosli, Ramly (2006)
Gaharu or it scientific named Aquilaria malaccensis is one of the most precious trees in the world. It is one of the most expensive natural products existing today. Gaharu is also known as Agarwood, eaglewood, aloeswood, oud, chen-xiang, and jingkoh. Gaharu grade C from peninsular Malaysia was used in this study. Conventional extraction method such as ultrasonic extraction and Soxhlet extraction is not effective, lower yield and the reaction time to produce gaharu essential oil take longer extraction time. Microwave assisted extraction method was identified as one of the extracting methods account to the economical, high yield and ease of the operation. By doing microwave assisted extraction, the time and temperature is observed by analyzing the data. The pressure performed at atmosphere (1atm), and temperature range is from 60°C to 100°C. For overall result, the yield percentage obtained is 0%. This is because the parameters that used in this experiment are not suitable for gaharu using microwave assisted extraction method. Low yield of the gaharu essential oils can be improved in future study by carrying out the research in larger scale.